Impact of salt, drought, heat and frost stresses on morphobiochemical and physiological properties of Brassica species: An updated review - Jan, Sohail Ahmad; Bibi, Nazma; Shinwari, Zabta Khan; Rabbani, Malik Ashiq; Ullah, Sana; Qadir, Abdul; Khan, Nadar (Journal of Pure and Applied Agriculture, 2024)
Abiotic stresses seriously impact crop productivity and agro-morphological and biochemical properties of all Brassica species. It also decreases the yield of many important Brassica species by disturbing their normal growth and development. In this review, we have highlighted the latest reports about the impact of different abiotic stresses on different growth stages and other morpho-physiological processes of important Brassica species such as canola/rapeseed (Brassica napus), indian mustard (Brassica juncea), Brassica oleracea and Brassica rapa. Several researchers reported that abiotic stresses affect the important morpho-biochemical processes such as shoot and root length, shoot fresh and dry weight, proline and relative water contents, chlorophyll amount, antioxidant enzymes activity of important Brassica species.